Chapter Bookkeeping as a 'key technology' of pre-modern commerce. Its relevance for the eco-nomic development in Europe - Denzel, Markus A. (Datini Studies in Economic History, 2023)
It is the aim of this paper to analyse the importance of (double-entry) bookkeeping for the economic development in Europe and its possible indirect influence on economic growth. Being one of the most important commercial techniques of the European merchants double-entry bookkeeping stayed in close relationship to the expansion of trade. So, the distribution of different bookkeeping techniques all over Western and Central Europe, took place, on one hand, through the extensive commercial contacts of Italian merchant-bankers with merchants of regions north of the Alps and because of the need of many non-Italian merchants to consolidate their commercial knowledge in Italy through specific studies and/or through acquiring practical knowledge. On the other, treaties on (double-entry) bookkeeping supported its diffusion. The study analyses examples of ledgers as 'mirrors' of their enterprises' activities, and it will be shown how such ledgers served as instruments for reducing various risks of entrepreneurial engagement. As a result it will become clear that the knowledge of the technique of double-entry bookkeeping was one of the preconditions of the commercial and, later on, the industrial expansion of the Europeans, which made a significant difference to other merchant cultures in the world.